Efficacy of Conventional Laser Irradiation Versus a New Method for Gingival Depigmentation (Sieve Method): A Clinical Trial - Houshmand, Behzad; Janbakhsh, Noushin; Khalilian, Fatemeh; Talebi Ardakani, Mohammad Reza (Journal of Lasers in Medical Sciences, 2017)
Introduction: Diode laser irradiation has recently shown promising results for treatment of gingival pigmentation. This study sought to compare the efficacy of 2 diode laser irradiation protocols for treatment of gingival pigmentations, namely the conventional method and the sieve method. Methods: In this split-mouth clinical trial, 15 patients with gingival pigmentation were selected and their pigmentation intensity was determined using Dummett’s oral pigmentation index (DOPI) in different dental regions. Diode laser (980 nm wavelength and 2 W power) was irradiated through a stipple pattern (sieve method) and conventionally in the other side of the mouth. Level of pain and satisfaction with the outcome (both patient and periodontist) were measured using a 0-10 visual analog scale (VAS) for both methods. Patients were followed up at 2 weeks, one month and 3 months. Pigmentation levels were compared using repeated measures of analysis of variance (ANOVA). The difference in level of pain and satisfaction between the 2 groups was analyzed by sample t test and general estimate equation model. Results: No significant differences were found regarding the reduction of pigmentation scores and pain and scores between the 2 groups. The difference in satisfaction with the results at the three time points was significant in both conventional and sieve methods in patients (P = 0.001) and periodontists (P = 0.015). Conclusion: Diode laser irradiation in both methods successfully eliminated gingival pigmentations. The sieve method was comparable to conventional technique, offering no additional advantage.